Kontribusi Pendidikan Agama Kristen Di Era Digital - Ester Nide (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Christian religious education has become an integral part of the education system in many countries around the world. However, with the development of digital technology, new challenges arise in providing relevant and effective Christian religious education to the digital generation. This study aims to investigate the contribution of Christian religious education in facing the digital era. This study uses a qualitative approach with in-depth interviews with Christian religious educators and analysis of related documents. The results of the study show that Christian religious education can make a significant contribution in the digital era by utilizing technology as a learning and communication tool. Christian religious education approaches that are centered on Christian beliefs, values, and teachings remain relevant in the digital era. Technology can be used to access a wider range of Christian religious texts and materials, connect students to the Christian community virtually, and provide platforms for more interactive discussion and reflection. However, this study also identified several challenges in implementing Christian religious education in the digital era, such as the risk of misuse of technology, the tendency to use it passively, and the difficulty in integrating the spiritual dimension in a virtual environment. In order to optimize the contribution of Christian religious education in the digital era, this research recommends adequate training for Christian religious educators in the use of technology, developing relevant and meaningful digital content, and careful monitoring of the use of technology in Christian religious education.